Media literacy and national security awareness: The formation of Chinese higher education groups' attitude to the Russia-Ukraine war. Issue 1 (2022) - Cheng, Lang; Bao, Ran
Abstract: With the development of information and communication technology, the opportunities for national citizens to freely participate in the discussion of political issues have been unprecedentedly expanded. Established in citizens' media literacy and national security awareness, this research explores the influence of these factors on media trust (domestic or overseas) and political information access among Chinese higher education groups (CHEG). This paper used the partial least square and structural equation method to discuss the factors that affect the formation of respondents' political attitudes by taking the recent Russia-Ukraine conflict as an example. The result shows that for CHEG, media literacy plays a positive role in their political information contact but does not affect their trust and choice of domestic and foreign media. Meanwhile, national security awareness also plays a positive role in their political information contact and the trust of domestic media. From the perspective of respondents' political attitudes, the more national security awareness and media literacy they have, the more they support Russia. On the contrary, the reduced awareness of national security makes them more willing to choose foreign media and therefore more supportive of Ukraine. In general, this paper reveals the important influence of national security awareness on the formation of political attitudes and illustrates the critical role of national ideological propaganda.